Depression and family arguments: disentangling reciprocal effects for women and men. (17th September 2019) - Wong, Jessie J; Frost, Nickolas D; Timko, Christine; Heinz, Adrienne J; Cronkite, Ruth
Abstract: Background: Depression is a debilitating condition that affects the individual and the family. Objective: This study sought to identify potential reciprocal influences between family arguments and depressive symptoms among clinically depressed patients over a 23-year span. Methods: The present study employed a longitudinal, observational design with 424 depressed patients. Separate cross-lagged path models examined longitudinal associations for women and men over 23 years while adjusting for age, income, and marital and parental status. Results: Among depressed men, more severe baseline depressive symptoms predicted more family arguments 10 years later. Among depressed women, more severe baseline depressive symptoms predicted fewer family arguments 1 year later, while more severe depressive symptoms at 10-year follow-up predicted more family arguments at 23-year follow-up. More family arguments predicted more severe depressive symptoms among women and men, with some variation in the time intervals of these associations. Conclusion: These findings suggest that while depressive symptoms may temporarily diminish family arguments among women, such symptoms were associated with more family arguments over longer time intervals. Moreover, family arguments put depressed men and women at risk for more severe depressive symptoms. These results support the use of screening for family arguments and interventions to help depressed individuals develop skills to manage interpersonal conflict.